Future-Generation Perception: Equal or Not Equal? Long-Term Individual Discount Rates for Poland - Monika Foltyn-Zarychta (Energies, 2021)
Energy-related investments gain increasing attention nowadays, particularly in Poland due to clean-energy investment needed to limit greenhouse gas emissions (GHG) and counteract climate change. However, economic appraisal is problematic: the longevity of impacts inextricably involves intergenerational ethical considerations. A crucial parameter is the choice of a discount rate. The predominant approach to estimate the discount rate in EU countries is the Ramsey rule, based on macroeconomic data, but not referring directly to society’s preferences. Those are considered by studies using surveys to elicit individual discount rates (IDR), but rarely concentrating on intergenerational time frame. The paper aims at delivering an insight into the intergenerational intertemporal preferences for Poland (households, n = 471) focusing on whether respondents are willing to declare zero discount rate intergenerationally and whether their choices differ between the short- and long-term perspectives and between human lives and money. To elicit IDR, two hypothetical investment scenarios were designed: lifesaving programs and lottery gains with delays from 10 to 150 years accompanied by attitude and socioeconomic questions. The results indicate that IDR follows hyperbolic time-decline, and a considerable share of respondents (around 20%) are willing to treat future generations as equally important in the case of human lives, while this proportion for monetary gains is two times lower. The IDR drivers differ between lives and money in respect of socioeconomic profile and attitude characteristics as well as between intragenerational and intergenerational time frames. The findings support (a) the rationale for distinct treatment of intergenerational allocations, (b) the divergence of preferences between public and private impacts, and (c) the switch from single to declining discount rate regime in Poland.